(untitled) (Research, Society and Development, 2023)
The work aims to identify the knowledge about environmental education of high school students from a state and private school in the city of Arapiraca-AL and Girau do Ponciano-Al, respectively, about the problems caused by the incorrect disposal of batteries. For that, a questionnaire was structured and given to the students to obtain the results. Through the application of the questionnaires, it was observed that of the total of 158 respondents (students from private and public schools), 75.3% dispose of batteries in common waste, demonstrating that they are unaware of the dangers that are caused by incorrect disposal or by not having a collection point close to their homes, since of the total of respondents, 91% say they do not have a collection point close to where they live. In the school environment, it was noticed that schools do not or do not include students in projects focused on the theme, the environment, since 86.7% answered not to participate in projects at school. Therefore, it is very important to carry out environmental education actions with students, incorporating the legislation Law No. 9,795/99 and Law No. 6,938/81, in addition to the measures established in the National Common Curricular Base and the inclusion of the Transversal Contemporary Themes; the local population of Arapiraca must also participate in environmental and health projects, especially regarding the importance of proper disposal of batteries.